Phytochemical Composition and Antioxidant Activity of Some Scorzonera Species - Erden, Yavuz; Kirbag, Sevda; Yilmaz, Okkes (Natl Acad Sciences India, 2013)
This study was carried out on the phytochemical composition (such as vitamins and flavonoids), element content and antioxidant activity of the Scorzonera suberosa (C. Koch), S. latifolia (Fisch. & Mey.) and S. laciniata (L.) species. The aerial parts of plant samples were used in the analyses. Species composition of vitamins, flavonoids, resveratrol and sugar were determined by using HPLC. Mineral analysis was performed using atomic absorption spectrometry. Antioxidant levels were determined by using DPPH free radical. In flavonoid structure of the aerial parts of the related species, different amounts of rutin, myricetin, morin, quercetin and kaempferol together with ergosterol, stigma sterol and beta-sitosterol as phytosterols, vitamin D, vitamin K, alpha-tocopherol and retinol as vitamins, and arabinose, fructose, glucose, sucrose and maltose as sugars were found. The mineral analyses was related to the existence of Ca, Na, K, Fe, Mn, Zn and Mg with different amounts in all of the three species. However, Cu, Co and Ni were not found. The free radical scavenging effect of the species showed a parallel increase in dose. Consequently, the phytochemical composition and the antioxidant activity of the species used in this study were determined.
Keywords: Scorzonera; Medicinal plant; Phytochemical composition; Antioxidant effect